2003
DOI: 10.1001/archpedi.157.8.773
|View full text |Cite
|
Sign up to set email alerts
|

A Reduced–Glycemic Load Diet in the Treatment of Adolescent Obesity

Abstract: An ad libitum reduced-GL diet appears to be a promising alternative to a conventional diet in obese adolescents. Large-scale randomized controlled trials are needed to further evaluate the effectiveness of reduced-GL and -glycemic index diets in the treatment of obesity and prevention of type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
232
1
13

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(255 citation statements)
references
References 40 publications
9
232
1
13
Order By: Relevance
“…The common or shared aetiologies of obesity and MS may also impact on who is targeted for obesity treatment and the management approach chosen. 33 The strengths of this study are recent data collection allowing assessment of MS prevalence within a background of high obesity prevalence and the narrow age range, which limits the effect of age-related differences, including the possible confounding of puberty on insulin resistance. The limitations of the study are the lack of a (non-overweight) control group to enable comparison and that the cut points used for MS definitions were not derived from local data.…”
Section: Discussionmentioning
confidence: 99%
“…The common or shared aetiologies of obesity and MS may also impact on who is targeted for obesity treatment and the management approach chosen. 33 The strengths of this study are recent data collection allowing assessment of MS prevalence within a background of high obesity prevalence and the narrow age range, which limits the effect of age-related differences, including the possible confounding of puberty on insulin resistance. The limitations of the study are the lack of a (non-overweight) control group to enable comparison and that the cut points used for MS definitions were not derived from local data.…”
Section: Discussionmentioning
confidence: 99%
“…There have been previous studies of low-GI diet in obese children (9-12) who had significant changes in body composition when they received instruction about this diet. A study of 14 obese children divided into two groups receiving a reduced-GL vs. reduced-fat diet by Ebbeling et al (12) found BMI and FM decreased more in the low-GL group at 12 mo. Intensive intervention by 12 dietary behavioral therapy counseling sessions for 6 mo followed by two dietary counseling sessions for 6 mo afterward may have caused this reduction in FM, not observed in our study.…”
Section: Articlesmentioning
confidence: 99%
“…However, the effectiveness of a low-GI diet in the treatment of pediatric obesity has not been well evaluated. There are few studies in obese children on BMI reduction (6)(7)(8) and fat mass reduction (9)(10)(11)(12), and some of these studies showed an improvement in insulin sensitivity (9,12); however, their sample sizes were quite small, and most of the studies were conducted in western countries and may not be applicable to Thai cuisine. In Thailand, the staple food is rice which has several varieties.…”
mentioning
confidence: 99%
“…Figure 4 models the short-term (1-year) results from these types of studies, translated to BMI percentiles. Figure 5 demonstrates results from all behavioral counseling studies among adolescents 86,88,104,105,107,108 that reported, or could be translated into, BMI percentiles. Most studies addressed extremely overweight patients, with short-term results showing modest to no change in BMI percentiles.…”
Section: Behavioral Counseling Interventionsmentioning
confidence: 99%